Early external‐environmental and internal‐health predictors of risky sexual and aggressive behavior in adolescence: An integrative approach. Issue 3 (31st August 2020) - Ellis, Bruce J.; Shakiba, Nila; Adkins, Daniel E.; Lester, Barry M.
Abstract: External predictive adaptive response (PAR) models assume that developmental exposures to stress carry predictive information about the future state of the environment, and that development of a faster life history (LH) strategy in this context functions to match the individual to this expected harsh state. More recently internal PAR models have proposed that early somatic condition (i.e., physical health) critically regulates development of LH strategies to match expected future somatic condition. Here we test the integrative hypothesis that poor physical health mediates the relation between early adversity and faster LH strategies. Data were drawn from a longitudinal study (birth to age 16; N  = 1, 388) of mostly African American participants with prenatal substance exposure. Results demonstrated that both external environmental conditions early in life (prenatal substance exposure, socioeconomic adversity, caregiver distress/depression, and adverse family functioning) and internal somatic condition during preadolescence (birthweight/gestational age, physical illness) uniquely predicted the development of faster LH strategies in adolescence (as indicated by more risky sexual and aggressive behavior). Consistent with the integrative hypothesis, the effect of caregiver distress/depression on LH strategy was mostly mediated by worse physical health. Discussion highlights the implications of these findings for theory and research on stress, development, and health.